QoS control by means of COPS to support SIP-based applications. - Salsano, S.
The COPS protocol has been designed to enable communication on the interface between the policy decision administrator and the policy enforcement devices in a policy-based networking environment. It can be recognized that on the same interface there is the need to transfer information related to the request of resource by QoS clients and for the allocation of resources by resource allocation servers (e.g., bandwidth broker) in a DiffServ network. Hence, it is sensible to add this resource allocation functionality in the COPS framework. In particular, there are at least two cases where it is sensible to use COPS. The first case is on the interface between an edge node and a resource control node for handling resource allocation in a network provider domain. The second case is on the interface between a customer (client of a QoS enabled network) and the network provider: here COPS can be used as a protocol to signal dynamic admission control requests. In this article we present the definition of a new COPS client type to support the above-mentioned functionality, then describe an application scenario where SIP-based IP telephony applications can use Diffserv-based QoS networks. Simple backward-compatible enhancements to SIP are needed to interact with COPS/Diffserv QoS. A testbed implementation of the proposed solutions is finally described
Keywords: COPS; DiffServ network; QoS control; SIP-based applications; Common open policy service; Dynamic admission control requests; Policy based networking environment; Policy decision administrator; Policy enforcement devices; Resource allocation functionality; Resource control node